Proposta interventiva no desempenho de variáveis cognitivas e motoras de pré-escolares - Daronch, Heitor dos Santos (2016)
The performance in cognitive and motor variables are preponderant factors for the development of the subject. This development is characterized by being an ongoing process that occurs throughout the life of the people. There are studies that have diagnosed a low level motor development in children. These low levels can lead to different problems such as a deficit in academic performance or diseases due to lack of adherence to the movement. In this sense, the objective is to evaluate the effects of an interventional proposal on the performance of cognitive and motor variables of preschool children. The study is characterized as experimental. The research group consisted of 24 children aged 5 to 6 years old from the Ipê Amarelo Infantile Education Unit of the Federal University of Santa Maria. The study participants were selected according to the pre-established criteria, for further division into experimental group 1, experimental group 2 and control group. Attention / concentration, fine motor and simple reaction time were evaluated by the Vienna Test System and the balance and oculomotor coordination by the Bruininsky-Ozeretsky Motor Performance Battery. Experimental group 1 underwent a motor activity intervention with emphasis on guided instruction and free education, and G2 underwent an intervention with emphasis on free teaching, both composed of 40-minute classes, 3 times a week, totaling 24 classes. In the statistical analysis, descriptive statistics were performed to represent the research groups. In order to perform the hypothesis tests, the sphericity test was performed initially, followed by the 2-way ANOVA. The results of the dissertation were divided into two articles: Article I, entitled "Intervention proposal for preschool children", with a detailed description of the methodology used in the intervention proposal. And Article II entitled "Effects of the intervention proposal on the performance of cognitive and motor variables of preschool children", with the application of the interventional proposal. The results of article II indicate significant improvement in favor of the group with interventional proposal only variable balance. It was concluded that the interventional proposal improved performance in the motor variable of preschool balance. However, the other variables did not show statistically significant improvements and this can be attributed to the environmental factors involved in the proposal.